Quality of Service, Purchase Interest, Brand Trust on Joyland Festival Concert Ticket Purchase Decision - Parasari, Nyoman Sri Manik; Pranajaya, I Kadek Widi; Maheswari, A.A. Istri Agung (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Concert organizers in Bali are increasing almost every year, this project requires consideration of many things that can affect the decision to buy tickets and from this the organizer relies on services such as event organizers to help run the project smoothly. Balinese entertainment and cultural performances attract the attention of tourists and increase the resources of local communities, so that performances and entertainment in Bali are increasingly prominent in the world of arts and are able to compete in their class. The purpose of this study is to analyze service quality, purchase interest, and brand trust on purchasing decisions for Joyland Festival concert tickets. This research method uses purposive sampling with a sample of 126 respondents with predetermined characteristics and this research data collection method is collected through questionnaires, using SmartPLS 4.0 analysis techniques. The results of this study indicate that purchase intention, brand trust, and service quality influence purchasing decisions. Due to adding factors that influence purchasing choices, it is hoped that future researchers can expand the scope of their research.